FLUVIAL PROCESSES AND MORPHOLOGY IN RIVER CHANNEL CONFLUENCES: A REVIEW - Dos Santos, Vanessa Cristina [UNESP]; Stevaux, Jose Candido [UNESP] (Uniao Geomorfologia Brasileira, 2017)
River channel confluences are sites with continuous changes in the flow structure and sediment transport. A network point of view confluences operate complex interactions between material and energy, provided by the combination of different flow patterns. This particular dynamic can be influential since ecological aspects of management and space occupy planning. In the last decades, scientific interest on geomorphological processes occurring in confluences channels has increased. This interest comes from the growing awareness that processes and morphology of the confluences summarize the characteristics of the upstream watersheds, at the same time they play an important role in the regulation of water and sediments circulating in the downstream river network. Several studies about fluvial processes and morphological at river channel confluences involve laboratory experiments, field research and simulations. Often these studies are a combination of some disciplines such as geomorphology, ecology, engineering, hydrology and sedimentology, evidencing the multidisciplinary character of the analysis of these complex environments. In Brazil, studies about geomorphological processes in river channel confluences are few and mostly developed in large rivers. This paper provides a succinct review and discussion of the current state of knowledge of river channel confluences.
Keywords: River Channel Confluences; Flow Structure; Morphology; Sediment Transport